Effectiveness of first and second‐line empirical treatment in Italy: Results of the European registry on Helicobacter pylori management. Issue 1 (23rd December 2022) - Gatta, Luigi; Nyssen, Olga P.; Fiorini, Giulia; Saracino, Ilaria Maria; Pavoni, Matteo; Romano, Marco; Gravina, Antonietta Gerarda; Granata, Lucia; Pellicano, Rinaldo; Gasbarrini, Antonio; Di Leo, Alfredo; Losurdo, Giuseppe; et al.
Abstract: Background and Aims: The optimal management of naïve and not naïve Helicobacter pylori patients remains unclear. Therefore, it is essential to evaluate whether the actual clinical practice mirrors the indications suggested by the guidelines. This study aimed to assess the effectiveness and the safety of the empirical first‐ and second‐line treatments prescribed to patients enroled at Italian centres participating in the European Registry on H. pylori Management (Hp‐EuReg). Methods: The Hp‐EuReg is an international multicentre prospective non‐interventional registry starting in 2013 aiming to evaluate the management of H. pylori infection by European gastroenterologists. Patients were registered in an e‐CRF by AEG‐REDCap. Variables assessed included demographics, previous eradication attempts, treatment regimen, effectiveness, and tolerance. Results: Overall, 3723 patients from 2013 to February 2021 were included: 2996 and 727 received an empirical first‐ and second‐line treatment, respectively. According to the modified ITT analysis, among the first‐line regimens, only the bismuth quadruple therapy with three‐in‐one‐single capsule (BQT‐TSC), the concomitant, and the sequential treatment ‐ all lasting 10 days ‐ achieved an eradication rate >90%. Among the second‐line regimens, only the 10‐day BQT‐TSC reported an effectiveness >90%. High‐dose PPI twice daily also significantly increased the effectiveness of some therapies. The BQT‐TSC was the regimen with the highest incidence of adverse events. Conclusions: Only quadruple therapies lasting at least 10 days achieved over 90% eradication rates among the empirical first‐ and second‐line regimens. It remains unclear whether high‐dose PPI twice daily can improve the efficacy of quadruple treatment. Abstract :